2007
DOI: 10.1016/j.ejvs.2006.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Late Outcome of Spinal Cord Stimulation for Unreconstructable and Limb-threatening Lower Limb Ischemia

Abstract: In CLI patients the beneficial effects of SCS persist far beyond the first year of treatment and major amputation becomes infrequent after the second year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In recent years the number of papers with optimistic results has been increasing [21,22,23]. In everyday surgical practice, most vascular surgeons in patients without the option for femorodistal reconstructions consider the application of drugs (antiplatelet agents or prostanoids), spinal cord stimulation, and hyperbaric oxigenotherapy, but these are still limited and with modest results [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…In recent years the number of papers with optimistic results has been increasing [21,22,23]. In everyday surgical practice, most vascular surgeons in patients without the option for femorodistal reconstructions consider the application of drugs (antiplatelet agents or prostanoids), spinal cord stimulation, and hyperbaric oxigenotherapy, but these are still limited and with modest results [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…SCS has been used for a variety of pain conditions with the most common indications in the United States being failed back surgery syndrome (FBSS) and complex regional pain syndrome (CRPS). Labeled indications are considerably broader in Europe, Canada, and Australia, where the evidence requirements for approval are different . As clinical experience and basic science have progressed, it has become apparent that the use of SCS in certain pathologies yields a higher success rate than in others.…”
Section: Indicationsmentioning
confidence: 99%
“…The utilization of SCS in treatment of CLI is supported by clinical studies (prevalently nonrandomized cohort studies and some RCTs) [8][9][10][11][12][13] and by microcirculatory studies, which have shown an increased number of perfused capillaries without an increase in their diameter; 14 an increase in capillary density at 3 months; 5 and an increase in the peak-rest erythrocyte velocity during reactive hyperemia. 15 The first edition of TASC, 2 however, available when the study was designed, concluded that SCS cannot be recommended on the basis of available studies.…”
Section: Discussionmentioning
confidence: 99%